Tree Biomass Estimation in Karst Forest of West Papua, Indonesia - Andes , Andes Hamuraby Rozak; Destri , Destri Destri; Zaenal , Zaenal Mutaqien (Forestry Department, University of Muhammadiyah Makassar, 2021)
Indonesia is estimated to have 14,5 million hectares of karst areas. The characteristic of karst vegetation is specific, one of which is the dominance of small trees. With all of the potency, their vegetation acts as a significant carbon sequester and store it in biomass. This study aims to estimate and discuss biomass estimation in the karst forest within the Nature Recreational Park of Beriat, a protected area in South Sorong, West Papua. A total of 28 plots were made in the forest using the purposive random sampling method. Tree biomass (DBH ≥10 cm) was estimated using five different allometric equations. The results showed that the biomass was estimated at ca. 264 Mg ha-1 (95 % CI: 135-454 Mg ha-1). While small trees (DBH 10 – 30 cm) only contribute 30 % of the total biomass, about 38 % of the biomass is the contribution of large trees (DBH >50 cm), where Pometia pinnata contributes ca. 39 % of the biomass at plot-level. The use of various allometric equations results in different biomass estimates and biases with deviations ranged from -14.78 % to +17.02 % compared to the reference equation. Therefore, the selection of allometric equations used must be considered carefully to reduce uncertainties in biomass estimation.